2008
DOI: 10.1007/s10286-008-0480-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of depression on heart rate variability during pregnancy

Abstract: Depression during pregnancy has been associated with a number of adverse outcomes, but the underlying physiological mechanisms involved remain unclear. The purpose of this study was to examine the effects of maternal depression during pregnancy on the autonomic modulation of heart rate, in a naturalistic setting. Eighty-one pregnant women were studied between 25 and 31 weeks of gestation and were identified as either Depressed (n = 46), or healthy, Control (n = 35), based on depression scores and lifetime psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…63,64 These changes appear to be attenuated in depressed pregnant women, who have higher heart rates and lower parasympathetic heart rate variability compared with nondepressed women. 65 No studies, to our knowledge, have measured sympathetic/parasympathetic balance in PPD, but major depression and anxiety are associated with reduced parasympathetic control in nonpregnant populations. 66,67 Studies linking diminished parasympathetic activity with depression and anxiety suggest that autonomic dysregulation may predispose women to mood disorders.…”
Section: Autonomic Nervous Systemmentioning
confidence: 99%
“…63,64 These changes appear to be attenuated in depressed pregnant women, who have higher heart rates and lower parasympathetic heart rate variability compared with nondepressed women. 65 No studies, to our knowledge, have measured sympathetic/parasympathetic balance in PPD, but major depression and anxiety are associated with reduced parasympathetic control in nonpregnant populations. 66,67 Studies linking diminished parasympathetic activity with depression and anxiety suggest that autonomic dysregulation may predispose women to mood disorders.…”
Section: Autonomic Nervous Systemmentioning
confidence: 99%
“…Tonhajzerova, Visnovcova, Jurko & Mestanik (2016) point to irregularities in the neurocardiac reflex system associated with depression as the mechanism underlying this pattern. Only one study has explored cardiac measures in pregnant women as related to antenatal depression, suggesting a similar pattern of higher heart rate and lower heart rate variability (Shea, et al, 2008). Everett, Mahendru, McEnierry, Wilkinson, & Lees (2013) reported that higher maternal heart rates during the second semester of pregnancy are positively associated with higher birth weight.…”
mentioning
confidence: 99%
“…A number of mental disorders have also been linked to detrimental cardiovascular changes in pregnancy. For example, maternal emotional distress or depressive symptoms are associated with abnormal cardiovascular function, such as more reduction in parasympathetic activity (Shea et al, 2008) and a larger increase in blood pressure (hypertension and preeclampsia; Kurki, Hiilesmaa, Raitasalo, Mattila, & Ylikorkala, 2000;Qiu, Sanchez, Lam, Garcia, & Williams, 2007;Qiu, Williams, Calderon-Margalit, Cripe, & Sorensen, 2009). Furthermore, both hypertension disorders (Robinson et al, 2009(Robinson et al, , 2013Whitehouse, Robinson, Newnham, & Pennell, 2012) and maternal emotional distress (R€ aikk€ onen, Seckl, Pesonen, Simons, & Van den Bergh, 2011; Van den Bergh, Mulder, Mennes, & Glover, 2005) during pregnancy are linked to adverse behavior and developmental outcomes in infancy, childhood, and adulthood.…”
mentioning
confidence: 99%